Enhanced and Synthetic Vision 2004 2004
DOI: 10.1117/12.554462
|View full text |Cite
|
Sign up to set email alerts
|

Latency requirements for head-worn display S/EVS applications

Abstract: NASA's Aviation Safety Program, Synthetic Vision Systems Project is conducting research in advanced flight deck concepts, such as Synthetic/Enhanced Vision Systems (S/EVS), for commercial and business aircraft. An emerging thrust in this activity is the development of spatially-integrated, large field-of-regard information display systems. Headworn or helmet-mounted display systems are being proposed as one method in which to meet this objective. System delays or latencies inherent to spatially-integrated, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
0
25
0
2
Order By: Relevance
“…40 In this experiment, synthetic terrain was rendered on the HWD. The alignment of the synthetic terrain to the real terrain (OTW is considered truth for this experiment) is dependent on the static boresighting as well as the system latency.…”
Section: Hwds For Spacecraftmentioning
confidence: 99%
“…40 In this experiment, synthetic terrain was rendered on the HWD. The alignment of the synthetic terrain to the real terrain (OTW is considered truth for this experiment) is dependent on the static boresighting as well as the system latency.…”
Section: Hwds For Spacecraftmentioning
confidence: 99%
“…Consistent definitions and measurement techniques as well as preliminary latency (time delay) requirements have been proposed for Head-Worn Display S/EVS applications. 11,17 Based upon the most stringent requirements for HMD applications of S/EVS (i.e., demanding tasks using a high resolution, large field-of-view head-worn display), the required system latency might be as low as 20 msec.…”
Section: Latencymentioning
confidence: 99%
“…An in-situ latency measurement technique -the so-called "windshield washer" test 11 -was used to measure the HWD latency. This test used the conformal runway scene (i.e., space-stabilized, boresighted symbology) and a grid pattern of 5 degree lines projected on the out-the-window simulator visual.…”
Section: Latencymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that it is desirable to have the HWD system latency no more than 20 ms. 24 Reducing the latency to 20 ms would result in more readable text and reduce blurring video artifacts. However, the minimal latency of a display refreshed at 60 Hz is 17 ms without processing, indicating a signficant challenge for video processing, etc.…”
mentioning
confidence: 99%